Advanced materials for the impeller in an ORC radial microturbine. (September 2017) - Hernandez-Carrillo, Isaias; Wood, Christopher J; Liu, Hao
Abstract: For distributed generation with low-temperature sources, the micro organic Rankine cycle is an exceptional option. However, an abundance of work remains to minimise its high cost; for example, the expander represents up to 70% of the total capital cost. This paper proposes the design of a lean radial microturbine, which reduces production costs through simplification strategies e.g. alternative materials for the impeller, since low-temperatures allow the possibility of using polymers. The candidate materials are a composite (PEEK-GF30) and a thermoplastic (ABS); aluminium is used as a reference. The study is developed in five stages, namely, heat-mass balance (H&MB), mean-line turbine design, 3D blading, fluid-structure interaction (FSI) and prototyping. A gross power and efficiency of 1.5kW and 70% are respectively targeted. R245fa is selected as working fluid. An impeller diameter of 49mm and a rotational speed of 36, 000rpm results from the mean-line design. A one-way fluid-structure interaction (FSI) is performed. The modelling delivers consistent results with the mean-line design in terms of boundary conditions and the turbine efficiency is forecast to be in the range 76-86%. Three situations are evaluated: full load operation, rotor blocked and 27% over-speed. Additionally, the above-mentioned three materials are evaluated. In total, nine scenarios are compared. The factor of safety is used as a unique parameter for comparison. The analysis confirmed that in the worst situation (over-speed), PEEK-GF30 is structurally 11% stronger than Aluminium whereas ABS is 40% weaker than Aluminium and both materials are sufficiently strong for the application. Due to the superior performance of PEEK-GF30 and the fact that ABS is considerably inexpensive; both alternative materials are selected for prototyping using automated machining and additive manufacturing respectively.